Compliance of medical practitioners with diabetic treatment guidelines in West Rand, Gauteng - Nneka J. Ohanson; Deidré Pretorius (South African Family Practice)
Background: Diabetes mellitus is increasing globally and is associated with multiple complications. Guidelines have been formulated to standardise care among people living with diabetes mellitus (DM), but research shows poor compliance with treatment guidelines. The aim of this study was to assess how well healthcare practitioners in a district hospital in Gauteng complied with the most recent diabetic treatment guideline, Society for Endocrinology Metabolism and Diabetes South Africa (SEMDSA) 2017.